2021
DOI: 10.1101/2021.01.30.428930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small Intestinal Resident Eosinophils Maintain Gut Homeostasis Following Microbial Colonisation

Abstract: SUMMARYIntestinal homeostasis following postnatal microbial colonization requires the coordination of multiple processes including the activation of immune cells, cell-cell communication, the controlled deposition of extracellular matrix, and epithelial cell turnover and differentiation. The intestine harbors the largest frequency of resident eosinophils of all homeostatic organs, yet the functional significance of eosinophil recruitment to this organ has long remained enigmatic. Eosinophils are equipped to bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(88 reference statements)
2
1
0
Order By: Relevance
“…Intestinal eosinophils upregulated ECM components such as collagens and laminins, as well as matrix metalloproteases. This indicates that eosinophils remodel the ECM, including the basement membrane, and is in line with a recent preprint article that used proteomics to find substantial changes of the intestinal ECM composition in the absence of eosinophils ( Shah et al, 2021 Preprint ). Several studies found that eosinophils affect the intestinal barrier ( Buonomo et al, 2016 ; Johnson et al, 2015 ; Singh et al, 2019 ).…”
Section: Discussionsupporting
confidence: 85%
“…Intestinal eosinophils upregulated ECM components such as collagens and laminins, as well as matrix metalloproteases. This indicates that eosinophils remodel the ECM, including the basement membrane, and is in line with a recent preprint article that used proteomics to find substantial changes of the intestinal ECM composition in the absence of eosinophils ( Shah et al, 2021 Preprint ). Several studies found that eosinophils affect the intestinal barrier ( Buonomo et al, 2016 ; Johnson et al, 2015 ; Singh et al, 2019 ).…”
Section: Discussionsupporting
confidence: 85%
“…Early studies on eosinophils have mostly focused on their role in clearance of helminths and on their contribution to allergic disorders. Their role in tissue tolerance shown in our study, as well as in a preprint study describing their contribution to the gut physiology (Shah et al, 2021), highlight previously unappreciated eosinophil functions. Mast cells and ILC2s are required for Sv clearance and have been shown to induce eosinophil accumulation (Mukai et al, 2017;Nussbaum et al, 2013).…”
Section: Discussionsupporting
confidence: 67%
“…Consequently, despite the microbiota-independent migration of eosinophils to the GI tract, microbiota colonization affects turnover, activation state, and phenotype of eosinophils, indicating a feedback loop mechanism by which microbiota and eosinophils are interconnected. An example of phenotypic change due to microbiota colonization is an increase in eosinophil subpopulations characterized by higher expression levels of SiglecF and CD11c, similar to that produced in inflammatory responses [ 149 ]. However, the molecular mechanism responsible for this interaction and cross signaling is still not fully understood.…”
Section: Eosinophils As Keepers Of the T H 1/t H 2 Balancementioning
confidence: 99%